Diagnostic performance of the Qiaprep amp Viral RNA UM kit for the detection of COVID-19 compared to RT-PCR - Becerril Vargas, Eduardo; Cojuc-Konigsberg, Gabriel; Braverman-Poyastro, Alan; Armendáriz Mendoza, Erick; Mujica Sánchez, Mario Alberto; García Colín, María Del Carmen; Chávez Morales, Hansel Hugo; Aguirre Pineda, José Nicolás; Ibarra Cobas, Luis Carlos (Frontiers in Medicine, 2022)
Background RT-PCR is the currently recommended laboratory method for diagnosing acute SARS-CoV-2 infection. Nevertheless, to carry out this assay, numerous manual steps are necessary, but they are long lasting and error-prone. A new sample preparation solution was launched, the Qiaprep & amp Viral RNA UM kit, that combines a short, liquid-based sample preparation with one-step RT-PCR amplification and detection of SARS-CoV-2. Such alternative allows reducing the handling of samples and obtaining a result in a shorter period of time. The objective of the study was to compare the performance of the kit with RT-PCR. Methods A prospective trial was carried out in the clinical microbiology laboratory of a tertiary care hospital. The pharyngeal and nasopharyngeal swabs included in the study were taken from patients who underwent medical consultation because compatible COVID-19 symptoms. Samples were processed simultaneously for the reference RT-PCR and by the QIA P&A kit. Results 190 samples were included in the clinical trial. The reference RT-PCR method indicated that 125 (66%) samples, out of the 190, were positive. The QIA P&A kit showed 112 positive samples for SARS-CoV-2. The QIA P&A kit has a sensitivity of 86% to detect SARS-CoV-2 and a 100% specificity, the positive predictive value was of 96%, the negative predictive value 78%, and the obtained Kappa value was 0,76. QIA P&A kit showed a lower mean cycle threshold compared with the diagnostic standard, with a statistically significant difference (p < 0.05). Conclusion The QIA P&A kit has an acceptable, yet not optimal performance for sample preparation and amplification of SARS-CoV-2 and further studying is required for it to be validated as a cost-effective, rapid diagnostic method for detecting infections.